Electronic Literature as Digital Humanities Contexts, Forms, and Practices - Grigar, Dene; O'Sullivan, James (Electronic Literature, 2021)
This book is available as open access through the Bloomsbury Open programme and is available on www.bloomsburycollections.com. Electronic Literature as Digital Humanities: Contexts, Forms & Practices is a volume of essays that provides a detailed account of born-digital literature by artists and scholars who have contributed to its birth and evolution. Rather than offering a prescriptive definition of electronic literature, this book takes an ontological approach through descriptive exploration, treating electronic literature from the perspective of the digital humanities (DH)--that is, as an area of scholarship and practice that exists at the juncture between the literary and the algorithmic. The domain of DH is typically segmented into the two seemingly disparate strands of criticism and building, with scholars either studying the synthesis between cultural expression and screens or the use of technology to make artifacts in themselves. This book regards electronic literature as fundamentally DH in that it synthesizes these two constituents. Electronic Literature as Digital Humanities provides a context for the development of the field, informed by the forms and practices that have emerged throughout the DH moment, and finally, offers resources for others interested in learning more about electronic literature.